2006
DOI: 10.1371/journal.pmed.0030444
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics of Artesunate and Dihydroartemisinin following Intra-Rectal Dosing of Artesunate in Malaria Patients

Abstract: BackgroundIntra-rectal artesunate has been developed as a potentially life-saving treatment of severe malaria in rural village settings where administration of parenteral antimalarial drugs is not possible. We studied the population pharmacokinetics of intra-rectal artesunate and the relationship with parasitological responses in patients with moderately severe falciparum malaria.Methods and FindingsAdults and children in Africa and Southeast Asia with moderately severe malaria were recruited in two Phase II s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
58
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(69 citation statements)
references
References 24 publications
7
58
1
Order By: Relevance
“…Analogous results have been reported for artesunate, another artemisinin derivative (23), where no significant relationships could be shown between parasite clearance and initial plasma concentrations of DHA or artesunate-DHA exposure (using AUC in the first 6 h). A semimechanistic model of parasite dynamics describing the early effect of artemether and DHA concentrations on the parasite density in malaria patients has recently been proposed (10).…”
Section: Discussionsupporting
confidence: 80%
“…Analogous results have been reported for artesunate, another artemisinin derivative (23), where no significant relationships could be shown between parasite clearance and initial plasma concentrations of DHA or artesunate-DHA exposure (using AUC in the first 6 h). A semimechanistic model of parasite dynamics describing the early effect of artemether and DHA concentrations on the parasite density in malaria patients has recently been proposed (10).…”
Section: Discussionsupporting
confidence: 80%
“…This means that gender did not affect or change the absorption, distribution and elimination of DHA in the human body. However, Simpson et al [19] suggested that the pharmacokinetic properties of DHA were affected only by gender and body weight in malarial patients. It may be caused by a different metabolism in healthy volunteers and malarial patients.…”
Section: Discussionmentioning
confidence: 99%
“…Xing et al [18] investigated the pharmacokinetic profile of b-DHA in rats after oral administration of 10 mg/ kg b-DHA and the mean values of C max and t max of DHA were 142.2 mg/l and 0.8 h, respectively. Simpson et al [19] studied the population pharmacokinetics of artesunate and DHA in malarial patients. They reported that the estimated elimination half-life of DHA was 43 min and the pharmacokinetic properties of DHA were affected only by gender and body weight.…”
Section: Introductionmentioning
confidence: 99%
“…The level of exposure to DHA was similarly higher in our children than in the healthy adults in our previous study (AUC 0-ϱ s, 382 and 198 ng ⅐ h/ml, respectively). Comparison of the PK data generated with patients to the data generated with healthy adults is a limitation, in that acute malaria alone may affect the disposition of artemisinin drugs (29). A strength of our comparison, however, is that the pediatric and adult studies used identical study designs.…”
mentioning
confidence: 99%